Chiral sensors for determining the absolute configurations of α-amino acid derivatives12. Issue 37 (11th September 2018) - Chen, Zhongxiang; Fan, Hongjun; Yang, Shiwei; Bian, Guangling; Song, Ling
Abstract : Two simple 1 H NMR tests give the absolute configurations of α-amino acids. Abstract : A simple strategy for configurational assignments of alpha-amino acids has been developed by comparison of the proton NMR chemical shift values of the alpha hydrogens of N -phthaloyl protected alpha-amino acids in the presence of ( R )-CSA 1 and ( S )-CSA 1, respectively. Highly resolved NMR spectra can be obtained directly on the mixed solution of the chiral solvating agents with N -phthaloyl protected alpha-amino acids in NMR tubes, giving well distinguishable proton signals without interference which dramatically improve the accuracy of assignment and hasten the assigning procedure. The strategy is widely applicable for varied natural and non-natural amino acids.